Matrix metalloproteinase 9 expression: new regulatory elements - Surgucheva, Irina (Springer-Verlag, 2010)
Retinal ganglion cells apoptosis is linked to matrix metalloproteinase 9 (MMP-9) controlled changes of extracellular matrix. Abnormal expression of MMP-9 is associated with glaucomatous alterations. Thus, the knowledge of MMP-9 regulation is important for the understanding the pathogenesis of glaucoma. Here, we investigated the role of 3′-untranslated regions (3′-UTR) and microRNAs in MMP-9 regulation. We used in vitro mutagenesis and Luc reporter system to identify regulatory elements in the 3′-UTR of MMP-9. microRNAs were analyzed by qRT-PCR, and their role was investigated with inhibitors and mimics. We identified targets for miRNAs in 3′-UTR of MMP-9 involved in the regulation of MMP-9 expression. We then isolated miRNAs from the optic nerve A7 astrocytes and 293 T cells and confirmed the role of mi340 in the regulation using specific inhibitors and mimics. The results obtained show a new miRNA-mediated mechanism of MMP-9 expression regulation.